Challenges and Strategies to Improve SIMRS Adoption for Digital Transformation of Indonesian Hospital Management - Maharani Putri; Dewa Ayu Indrayani; Dyah Ayu Wulansari; Eka Wardhana Lestari; Farida Yuliaty; Kosasih; Vip Pratama (Lembaga Bale Literasi, 2026)
The use of Hospital Management Information Systems (SIMRS) has become increasingly important in supporting the digital transformation of healthcare services; however, its implementation continues to face various challenges, including limited infrastructure, user resistance, as well as security and regulatory issues that impact service quality. This study aims to analyze the challenges in SIMRS adoption and to formulate comprehensive strategies for improving its implementation. The method employed is a systematic literature review using content analysis and narrative synthesis of relevant literature. The results indicate that SIMRS is capable of enhancing operational efficiency, data accuracy, and service coordination, yet its implementation is still hindered by technical, organizational, and human resource factors. The required strategies include strengthening digital infrastructure, improving human resource capacity, reinforcing data security, conducting periodic system evaluations, and ensuring adaptive policy support. Therefore, the successful implementation of SIMRS requires a holistic and sustainable approach to provide optimal benefits in improving the quality of healthcare services.